The Study Regarding Social Media Adoption on Business Performance in Micro Small and Medium Enterprises Using a Service-Dominant Logic View (Empirical Study of Micro Small and Medium Enterprises) - Saptarani, Amanda Anisa; Tae Ferdinand, Agusty (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
This research aims to develop a conceptual model based on Social Media Adoption. Social Media Adoption itself is a variable that is expected to improve MSME business performance. In total, there were 210 MSME owners and MSME managers involved in this research activity. The Structural Equation Modeling (SEM) method was adopted as software to assist in testing models and hypotheses. Structural Equation Modeling (SEM) analyzed 150 questionnaires. The findings in this research are that Social Media Adoption has no effect on Business Performance in MSMEs. Commercial Value Accentuation and Innovation Capability are known to show that both can improve business performance, so this can be used as input for MSME managers to be able to benefit from the sales activities they carry out. The rejection of the hypothesis provides room for further research. The Bengkulu MSME sample framework limits the generalization power of the Commercial Value Accentuation concept, which then requires replication to achieve even broader generalizations. The theoretical implications of this research relate to strengthening the application of SDL theory in marketing studies. There are practical managerial implications for MSME entrepreneurs who want to improve Business Performance. This study explains the role of Commercial Value Accentuation and Innovation Capability on Business Performance. The conceptual model of this research was tested on a sample of MSMEs in the food and beverage sector from Bengkulu Province.